Sublittoral seaweed flora of the St. Martin’s Island, Bangladesh - Towhidy, Abdul Aziz Syntheia; Alfasane, Md Almajaddade (Bangladesh Journal of Botany, 2018)
Investigation on the sublittoral seaweed flora collected from 0.5 to 10 m depth during late March and April, 2013 from six localities around the St. Martin’s Island, Bangladesh has revealed the presence of 39 seaweed taxa, 12 under Rhodophyceae, 11 under Chlorophyceae and 16 under Phaeophyceae. Of these Avrainvillea amadelpha (Montagne) Gepp et Gepp (green), Pocockiella variegata (Lamx.) Papenfuss, Spatoglossum asperum J. Ag., Spatoglossum variabile Figari et De Notaris and Sargassum pallidum (Turner) C. Agardh (browns) are new records for Bangladesh.